COVID-19 PANDEMIC’S IMPACT ON TOURISM IN POLAND IN MARCH 2020 - Bartosz KORINTH; Ruwan RANASINGHE (Geo Journal of Tourism and Geosites, 2020)
The outbreak of Coronavirus Covid-19 pandemic caused global economic gloom in the first quarter of 2020. This crisis has particularly impacted tourism, which is the subject of this paper. Data regarding air traffic in March 2020 compiled by Polish Air Navigation Services Agency has been put to a detailed analysis. Accommodation occupancy rate in this period was analysed using statistics presented by STR company. The analyses’ conclusion clearly indicates on significant decrease in Poland’s tourism in March 2020. Occupancy rate declined in about 40% in comparison to data from last year, with fall in air traffic on Polish airports (resulting from stopping international air links) in about 80-90% in comparison to the same period last year.